(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The main purpose of this article is an analysis of social insurance in various kinds of employment forms. The text includes general information about social insurance and how insurance system in Poland was created. The authorintroduces law aspects and contributions duty of popular employment forms. The paper also compares cost of the social insurance contributions in various kinds of employment forms.